Abitudini, opinioni e dimostrazioni: il faticoso esercizio della ragione nella Guida dei perplessi di Maimonide - Benedetto, Marienza (E-theca OnLineOpenAccess Edizioni, 2026)
The article aims to show how, for Maimonides, the exercise of reason is by no means natural. It involves, in addition to a personal predisposition, a long philosophical training, which leads from logic to metaphysics. Nevertheless, there are truths that cannot be known through the demonstrative method: in such cases, dialectic comes to the rescue, which yet Maimonides always criticizes in the arguments of the theologians.